2001
DOI: 10.4049/jimmunol.167.10.5832
|View full text |Cite
|
Sign up to set email alerts
|

Rejection of Intraocular Tumors by CD4+ T Cells Without Induction of Phthisis

Abstract: Immune privilege of the eye protects against sight-threatening inflammatory events, but can also permit outgrowth of otherwise nonlethal immunogenic tumors. Nonetheless, ocular tumor growth can be controlled by cellular immune responses. However, this will normally result in phthisis of the eye, in case tumor rejection is mediated by a delayed-type hypersensitivity response orchestrated by CD4+ T cells. We now show that intraocular tumors can be eradicated by CD4+ Th cells without inducing collateral damage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
47
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 20 publications
(15 reference statements)
3
47
0
Order By: Relevance
“…The rejection of intraocular Ad5E1 tumors is unique, as it appears to be primarily mediated by CD4 ϩ T cells and not CD8 ϩ T cells (9). Although intraocular Ad5E1 tumors undergo rejection in mice depleted of CD8 ϩ T cells (9), there is evidence that CD8 ϩ T cells might play an ancillary role in Ad5E1 tumor rejection. Schurmans et al indicated that CD8 ϩ T cells were present in intraocular Ad5E1 tumors (9).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The rejection of intraocular Ad5E1 tumors is unique, as it appears to be primarily mediated by CD4 ϩ T cells and not CD8 ϩ T cells (9). Although intraocular Ad5E1 tumors undergo rejection in mice depleted of CD8 ϩ T cells (9), there is evidence that CD8 ϩ T cells might play an ancillary role in Ad5E1 tumor rejection. Schurmans et al indicated that CD8 ϩ T cells were present in intraocular Ad5E1 tumors (9).…”
mentioning
confidence: 99%
“…Once CD8 ϩ T cells are primed, the depletion of CD4 ϩ T cells does not affect the effector function of CD8 ϩ T cells (26). The rejection of intraocular Ad5E1 tumors is unique, as it appears to be primarily mediated by CD4 ϩ T cells and not CD8 ϩ T cells (9). Although intraocular Ad5E1 tumors undergo rejection in mice depleted of CD8 ϩ T cells (9), there is evidence that CD8 ϩ T cells might play an ancillary role in Ad5E1 tumor rejection.…”
mentioning
confidence: 99%
See 3 more Smart Citations